2016
DOI: 10.14421/ajis.2016.541.95-121
|View full text |Cite
|
Sign up to set email alerts
|

Abuse of Islamic Law and Child Marriage in South-Sulawesi Indonesia

Abstract: Abstract:This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…In South Sulawesi, A study reported the practice of child marriage among Buginese and Makassarese to be socially and culturally supported. People often believe that the sooner women are married, the better their economic and financial position will be, as well as the family's honor [12] . However, when women marry late or stay single, it is said their prosperity and luck are ‘closed and late’ which means that it can bring shame to family honours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Sulawesi, A study reported the practice of child marriage among Buginese and Makassarese to be socially and culturally supported. People often believe that the sooner women are married, the better their economic and financial position will be, as well as the family's honor [12] . However, when women marry late or stay single, it is said their prosperity and luck are ‘closed and late’ which means that it can bring shame to family honours.…”
Section: Discussionmentioning
confidence: 99%
“…They tend to seek normative religious-based texts which eventually claim the truth based on Islamic teaching. For them, women and men can marry if they have already achieved aqil baligh , without considering their age [12] .…”
Section: Discussionmentioning
confidence: 99%
“…42 Selain itu, pilihan untuk kawin lari tidak hanya disebabkan oleh keengganan orang tua karena status sosial, tetapi juga karena pilihan orientasi seksual yang berbeda dari orang kebanyakan 43 dan usia anak yang masih belia. 44 Jika diikuti makna kawin lari yang dilakukan jauh dari kediaman orang tua dan dengan wali perempuan yang juga tidak diketahui hubungannya dengan pihak perempuan atau bahkan pernikahan itu tidak dicatatkan, maka secara umum marlojong tidak termasuk pada jenis kawin lari seperti ini. Marlojong umumnya adalah semata cara adat menyelesaikan keengganan wali untuk menikahkan anaknya tanpa mereka harus mengajukannya ke pengadilan agama.…”
Section: Marlojong Dalam Sudut Pandang Hukum Islamunclassified
“…Pemmali culture can play a role in ensuring that, as one of the factors, child marriage increases sharply in the Religious Courts. As the results of research conducted by Salenda (2016) in his writings "Abuse of Islamic Law and Child Marriage in South Sulawesi, Indonesia" that child marriage in the Bugis community in South Sulawesi cannot be separated from 'pemmali' especially girls proposed for the third time.…”
Section: Introductionmentioning
confidence: 99%